Islam and Pancasila: Perspective of Indonesian Postgraduate Muslim Students - Toba Sastrawan Manik; Mukhamad Murdiono; Muhammad Andhika (Sospol : Jurnal Sosial Politik, 2021)
Pancasila as the basis of the state faces debates from nationalists and Islamic ideology followers in Indonesia. This is influenced by the development of theorizing about secularism, nationalism and theocracy. Considering the threat to the rise of communism and radicalism, this study aims to analyze the attitudes of Indonesian Moslem postgraduate students towards the principles of Pancasila. The number of samples in this study were 122 people from various Indonesian universities who were determined by random sampling. The data was distributed via Google Form and processed qualitatively descriptively. This study found that the majority of postgraduate Moslem students accepted affection, cognition and conation of each Pancasila precept. The level of respondent acceptance of Pancasila was 70-90%. There were some people who still do not accept Pancasila as an ideology but it was only in small number, 2.45% for those who strongly disagree and 7.42% who disagree. Pancasila is accepted by most Indonesian Moslem postgraduate students. The results of the research contribute in providing a new understanding of Pancasila as well as the young generation of Moslem.  However, there is many limitation in this research in reaching bigger and wider respondents. Further research on this topic is very welcomed.